Strategi Movie Learning Dalam Pembelajaran Akidah Akhlak - Siti Fatimah; Muhammad Zulkifli (Institut Agama Islam Darussalam Martapura, 2021)
Abstract: Inappropriate strategy implementation in learning activities will have an impact on low motivation and enthusiasm for student learning during the learning process. To overcome these problems, it is necessary to choose the right strategy. In this article, the focus is on discussing movie learning strategies to overcome problems of interest in learning. Sources of data in this study used books and scientific journals related to learning strategies. In this study using the library research method to obtain information about the nature of learning strategies and the effectiveness of movie learning strategies that can arouse students' interest in learning the subject of moral ethics.Keywords: Movie Learning Strategy, Aqidah Akhlak,